Characterization of anti-soybean agglutinin (SBA) IgY antibodies: a new strategy for neutralization of the detrimental biological activity of SBA - Ruiz Díaz, Nancy; Cisternas, Carlos; Silva, Mauricio; Hernández, Adrián; Chacana, Pablo (Frontiers in Veterinary Science, 2024)
Anti-Soybean agglutinin (SBA) IgY was produced and its potential to neutralise haemagglutinating activity of SBA in vitro was tested. 35-week-old hens [treatment (n=5) and control (n=5)] were immunised with SBA or injected with saline 4 times every 15 days. Eggs were collected after the last immunisation and IgY was extracted by the PEG method. Serum anti-SBA IgY titres in immunised hens increased after the first immunization and reached a plateau between days 45 and 60. In contrast, specific IgY titres in the control group remained at basal levels throughout the evaluation. Average IgY titres were significantly higher in the treatment group on days 15, 30, 45 and 60. Total IgY content in the egg yolk extract were 38.7± 1.6 and 37.7± 1.5 mg/mL for the treatment and control group respectively. The specific anti-SBA IgY titre detected in the egg yolk extract was significantly higher (p < 0.001) for hens in the treatment compared to control group, with OD450nm values of 0.98 0.05 and 0.058 0.02, respectively. The specificity of anti-SBA IgY was confirmed by Western blot, and the inhibition of SBA-induced haemagglutination in vitro was compared with D-galactose, a known molecule that binds to SBA and blocks its binding to erithrocytes. The inhibition of SBA-induced haemagglutination by the anti-SBA IgY reached 512 units of haemagglutination inhibition (UHI), compared to 8 or 256 UHI, respectively, when IgY from control chickens or Dgalactose was used. Thus, anti-SBA IgY antibodies were efficiently produced in large quantities and effectively inhibited SBA-induced haemagglutination in vitro.